Gangguan Ginjal Akut pada Anak: Faktor Risiko dan Tatalaksana Terkini - Virgin V. A. Karundeng; Valentine Umboh; Rocky Wilar (e-CliniC, 2024)
Abstract: Acute kidney injury (AKI) is defined as an acute drop in renal function and is determined by creatinine serum and urine output. Several studies conclude that the risk factors of AKI in children are differentiated according to its etiology.The management of AKI as recommended by KDIGO is according to the stadium. This study aimed to determine the risk factors and the current management of AKI in children. This was a literature review study conducted by searching literatures from Pubmed and Google Scholar. The results obtained 17 literatures related to the topic. The most common pre-renal and renal risk factors were sepsis and nephrotoxic medications respectively. Sepsis, shock, and gastroenteritis were found significantly related to the stadium of AKI in children. Current management of AKI in children was the use of dextrose in normal saline mixed with 3% of diluted Nacl to correct hypernatremic dehydration; the use of peritoneal dialysis for infant below 5 y.o, and the use of CARPEDIEM as the new CRRT for children <5kg; the use of caffeine citrate for neonates to prevent AKI. In conclusion, the most common risk factor according to the etiology of AKI in children is sepsis. The current managements are to correct AKI according to its etiology and stadium and to prevent AKI occurence in high-risk neonates. Keywords: acute kidney injury; risk factors; current management; children   Abstrak: Gangguan ginjal akut (GnGA) didefinisikan sebagai penurunan fungsi ginjal mendadak yang ditentukan oleh serum kreatinin dan output urin. Beberapa penelitian menyimpulkan bahwa faktor risiko GnGA pada anak dibedakan berdasarkan etiologinya, dan tatalaksana GnGA yang direkomendasikan oleh KDIGO disesuaikan dengan stadiumnya. Penelitian ini bertujuan untuk mengetahui faktor risiko dan tatalaksana terkini GnGA pada anak melalui suatu literature review. Hasil penelitian mendapatkan 17 literatur dari Pubmed dan Google Scholar. Faktor risiko pra-renal dan renal dari GnGA pada anak ialah sepsis dan penggunaan obat nefrotoksik secara berurut. Sepsis, syok, dan gastroenteritis berhubungan dengan stadium GnGA pada anak. Terapi terkini GnGA pada anak ialah penggunaan dekstrosa dalam normal salin yang dicampur diluted Nacl 3%, untuk memperbaiki dehidrasi hipernatremik; penggunaan peritoneal dialisis untuk bayi <5 tahun dan penggunaan CARPEDIEM sebagai CRRT untuk bayi <5kg; penggunaan kafein sitrat dapat mencegah GnGA pada neonatus. Simpulan penelitian ini ialah faktor risiko yang paling umum berdasarkan etiologi GnGA pada anak ialah sepsis. Terapi terkini ialah mengoreksi GnGA menurut etiologi dan stadiumnya serta mencegah terjadinya GnGA pada neonatus yang berisiko tinggi. Kata kunci: gangguan ginjal akut; faktor risiko; tatalaksana terkini; anak